2019
DOI: 10.1177/2058460119840969
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation force impulse (ARFI) shear wave elastography of the bowel wall in healthy volunteers and in ulcerative colitis

Abstract: Background: Acoustic radiation force impulse (ARFI) elastography is a non-invasive, ultrasound-based approach of evaluation of tissue elasticity. It has not yet been systematically applied to the bowel wall. Purpose: To perform ARFI elastography of the bowel wall in healthy volunteers and patients with ulcerative colitis (UC). Material and Methods: A high-frequency ultrasound (with bowel wall thickness and vascularization score) and an ARFI elastography of the bowel wall were performed in 20 patients with UC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 21 publications
0
23
2
Order By: Relevance
“…The average value of E was 6.38±1.35 kPa in the normal intestine of healthy volunteers (with a sample size of 59 for the TI), which was higher than that in our study (3.84±1.84 kPa), and which may be related to the type of US device and the different sample size. A study conducted by Goertz et al (11) using acoustic radiation force impulse (ARFI) showed that normal SWV values of the TI were 1.6±0.35 m/s (compared with 1.08±0.25 m/s in this study). However, they investigated only 13 healthy volunteers and mainly focused on pathological states.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…The average value of E was 6.38±1.35 kPa in the normal intestine of healthy volunteers (with a sample size of 59 for the TI), which was higher than that in our study (3.84±1.84 kPa), and which may be related to the type of US device and the different sample size. A study conducted by Goertz et al (11) using acoustic radiation force impulse (ARFI) showed that normal SWV values of the TI were 1.6±0.35 m/s (compared with 1.08±0.25 m/s in this study). However, they investigated only 13 healthy volunteers and mainly focused on pathological states.…”
Section: Discussioncontrasting
confidence: 46%
“…Several published articles have also confirmed that elastography can stably provide quantitative elasticity information in the IBD bowel wall. Goertz et al (11) found that the mean ARFI values in an ulcerative colitis group (1.97±0.64 m/s, n=20) were higher than those of a healthy control group (1.75±0.51 m/s, n=13). Ding et al (18) indicated that the optimal cut-off value was reached when the shear wave velocity exceeded 2.73 m/s in evaluating and differentiating intestinal stenosis in Crohn's disease, with a sensitivity of 75%, a specificity of 100%, and an accuracy of 96%.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We were able to find one study on ultrasound elastography in ulcerative colitis [ 32 ]. Goertz et al performed ARFI shear wave elastography in 20 UC patients.…”
Section: Resultsmentioning
confidence: 99%